DAMPAK PANDEMI COVID 19 TERHADAP KINERJA PERBANKAN STUDI KASUS PADA BANK DENGAN KATEGORI KELOMPOK BANK MODAL INTI (KBMI) 4 DI INDONESIA - Saifuddin Anshori; C. Ambar Pujiharjanto; Sri Dwi Ari Ambarwati (FEB Universitas Sam Ratulangi Manado, 2022)
This study aims to determine the impact of the COVID-19 pandemic on banking performance in terms of six variables, namely NPL, LDR, ROA, ROE, BOPO, and CAR. This study used the Core Capital Bank Group 4 or KBMI-4 as the research sample which was tested using a paired t-test. The results of this study are that there are differences between NPL, LDR, ROA, ROE, and BOPO, before and during the covid-19 pandemic. While the CAR does not have a significant difference. LDR, ROA, and ROE during the pandemic are lower than before the pandemic, while NPL and BOPO during the pandemic are higher than before the pandemic